2011
DOI: 10.1177/0300985811431446
|View full text |Cite
|
Sign up to set email alerts
|

Of Mice and Microflora

Abstract: The phenotype of genetically engineered mice is a combination of both genetic and environmental factors that include the microflora of the mouse. The impact a particular microbe has on a mouse reflects the host-microbe interaction within the context of the mouse genotype and environment. Although often considered a confounding variable, many host-microbe interactions have resulted in the generation of novel model systems and characterization of new microbial agents. Microbes associated with overt disease in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 91 publications
1
25
0
1
Order By: Relevance
“…Consistent with prior studies (Treuting et al, 2012), we found little if any T.mu in the small intestine of T.mu -bearing animals prompting us to focus mainly on immune changes in the colonic mucosa (data not shown). To directly address whether the presence of T.mu was responsible for the expansion of gut tissue-resident immune cells and increased IgA levels, we colonized commercial B6 mice with purified T.mu .…”
Section: Resultssupporting
confidence: 90%
“…Consistent with prior studies (Treuting et al, 2012), we found little if any T.mu in the small intestine of T.mu -bearing animals prompting us to focus mainly on immune changes in the colonic mucosa (data not shown). To directly address whether the presence of T.mu was responsible for the expansion of gut tissue-resident immune cells and increased IgA levels, we colonized commercial B6 mice with purified T.mu .…”
Section: Resultssupporting
confidence: 90%
“…66 These intraluminal protozoa were not associated with any clinical signs or evidence of host response or tissue damage.…”
Section: Resultsmentioning
confidence: 91%
“…P. pneumotropica is a gram-negative, non-spore-forming opportunistic pathogen with high prevalence in murine research colonies. 66 Transmission occurs through direct contact, although its true nature as a primary pathogen is questionable. Outbreaks of P. pneumotropica have been reported in numerous GEM and spontaneous immunodeficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second mouse was diagnosed with pulmonary Pneumocystis murina infection, which is characterized by alveolar filling and distention by large macrophages, fungal organisms and debris. 28,29 Interestingly, only a small number of alveolar macrophages had intense immunostaining (Figure 1O) whereas many lacked arginase-I immunostaining.…”
Section: Resultsmentioning
confidence: 98%